2019
DOI: 10.5114/aoms.2017.68409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the incidence of new malignancies in diabetic patients in urban and rural populations in Poland in the years 2008–2014 based on the database of the National Health Fund

Abstract: A b s t r a c tIntroduction: Many epidemiological studies show a correlation between the risk of cancer and type 2 diabetes mellitus in various populations. Material and methods: The material was obtained from the database of the National Health Fund. This publication presents a comparison of the incidence of new malignancies in rural and urban populations of diabetic patients in Poland based on the database of the National Health Fund for the period between 1. 05.2008 and 30.09.2014. Results: Comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The association between T2DM and a greater incidence of cancer has been observed in several studies and has been specifically corroborated for several types of tumours, 8–12 but the relationship of T2DM with cutaneous melanoma remains controversial. A recent meta‐analysis of nine cohort studies concluded that T2DM might be an independent risk factor for malignant melanoma, even when the results were adjusted for age and obesity.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The association between T2DM and a greater incidence of cancer has been observed in several studies and has been specifically corroborated for several types of tumours, 8–12 but the relationship of T2DM with cutaneous melanoma remains controversial. A recent meta‐analysis of nine cohort studies concluded that T2DM might be an independent risk factor for malignant melanoma, even when the results were adjusted for age and obesity.…”
Section: Discussionmentioning
confidence: 82%
“…7 Patients with T2DM increasingly present several types of solid tumours, although there have also been reports of a paradoxical reduction in the incidence of prostate cancer. [8][9][10][11][12] However, the relationship between T2DM and cutaneous melanoma has scarcely been studied. A recent meta-analysis has suggested that T2DM represents a risk factor for melanoma, although the findings of each study included in the meta-analysis were inconsistent.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial hypertension and diabetes mellitus are well known as risk factors for anthracycline-induced cardiotoxicity [13]. Wierzba et al showed correlation between different types of cancers and diabetes both in urban and rural areas [14].…”
Section: Discussionmentioning
confidence: 99%
“…The method used is the secondary statistical analysis of data reported to the national payer -the National Health Fund (NFZ) by medical institutions with an indicated diagnosis of lip, oral cavity and pharyngeal cancer in the years 2008-2017 based on ICD-10 classification of diseases. This method has been already used for similar analyses [5][6][7][8]. The analysis included all the reported information on interventions in patients undergoing therapy after a diagnosis of lip, oral cavity and pharyngeal cancer (according to ICD-10 = C00.X -C14.X [9, 10] as the main reason for the intervention; the NFZ databases record all patients whose therapy was financed from the public funds).…”
Section: Methodsmentioning
confidence: 99%